Tinjauan Literatur Sistematis dan Kajian Bibliometrik Peran Stakholder dalam Perkembangan Pariwisata Menggunakan Analisis Jaringan Sosial - Redha Maulana Yusra; Hidayatul Fajri (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
This study aims to determine the role of stakeholders in tourism management using social network analysis. The research was carried out through systematic literature reviews and bibliometric studies, to identify trends and patterns in research related to tourism management by involving stakeholders. This research was conducted from 06/May/2023 to 06/April/2023. To describe the issues mentioned above about the role of stakeholders in the development of Tourism Using Social Network Analysis. It therefore extracts data from Google Scholar as the leading indexing service for peer-reviewed publications. Of the more than 94 titles on Google Schooler using the Publish of Perish application related to the keywords "Social Network Analysis" and "Tourism", there are only 13 article titles related to Social Network Analysis" and "Tourism. From the bibliometric analysis of data extracted from Google Scholar using the Publish of Perish and Mendeley applications, after the filtering stage was carried out, the Vosviewer Alication was used, it was seen that there were 2 clusters of concern, namely (1) Tourism, Coastal and social network analysis. 2) antraction, institutional. It can be concluded that research using the keywords social networks and tourism is still rarely published in Google Scholar searches.